1996
DOI: 10.1021/bi960712v
|View full text |Cite
|
Sign up to set email alerts
|

Annexin V Inhibition of Factor IXa-Catalyzed Factor X Activation on Human Platelets and on Negatively-Charged Phospholipid Vesicles

Abstract: Annexin V was found to inhibit factor IXa-catalyzed factor X activation on both thrombin-activated human platelets and artificial lipid vesicles containing phosphatidylserine, supporting previous observations of the importance of negatively-charged lipid in potentiating the reaction. Annexin V reduced the Vmax of factor X activation in factor IXa titrations on the platelet surface with an IC50 of 4 nM in the absence of thrombin-activated factor VIII (factor VIIIa), and 4.5 nM in its presence, whereas there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 27 publications
6
27
0
1
Order By: Relevance
“…50 Likewise, annexin V is an incomplete inhibitor of the factor Xase complex on platelet membranes. 51 Our results, indicating that inhibition of the prothrombinase complex exceeds 80% at 60 nM annexin V only when the curvature of the membrane is minimal and the PS content is 15%, are in agreement with these prior studies. The ␤ 2 -glycoprotein I binds to PS-containing membranes and other negatively charged lipid-containing particles such as lipoproteins.…”
Section: Discussionsupporting
confidence: 93%
“…50 Likewise, annexin V is an incomplete inhibitor of the factor Xase complex on platelet membranes. 51 Our results, indicating that inhibition of the prothrombinase complex exceeds 80% at 60 nM annexin V only when the curvature of the membrane is minimal and the PS content is 15%, are in agreement with these prior studies. The ␤ 2 -glycoprotein I binds to PS-containing membranes and other negatively charged lipid-containing particles such as lipoproteins.…”
Section: Discussionsupporting
confidence: 93%
“…The inhibition curves of FVIIIa in the presence of EGR-FIXa and FX are quite steep, and the slope of the curve is greater than that described by a simple competitive inhibition model. Thus, our equilibrium binding studies and competition studies further clarify that annexin V has an effect only on active cofactor (FVIIIa), similar to the effects we have reported on FIXa binding (53) and FX binding (23). We recently reported (53) on the kinetic effects of annexin V on FVIIIa enhancement of F-X activation on activated platelets and phospholipids.…”
Section: Discussionsupporting
confidence: 87%
“…Previously we have shown that annexin V is a very potent inhibitor of both FX and prothrombin binding to activated platelets with IC 50 of 3.1 and 2.6 nM, respectively (23). We have also shown that annexin V affects the affinity and stoichiometry of FIXa interaction with platelets and phospholipids, and we have concluded that the interaction of both the enzyme (FIXa) and the substrate (FX) is mediated in a complex manner by both phospholipids and perhaps a protein receptor (53). Studies from other laboratories (52,54) have reported that annexin V interferes with FV and FVa binding and prothrombinase activity on both the platelet membrane and phospholipid vesicles.…”
Section: Binding Of Pro-cofactor (Factor Viii) and Active Cofactor (Fmentioning
confidence: 70%
“…FVIII (200 U/ ml) was incubated 1 minute at 37°C with thrombin (0.5 U/ml) and an additional minute with hirudin (5 U/ml) immediately before addition to reaction mixtures. Reactions were stopped after 2-3 minutes and were analyzed for FXa generated by chromogenic substrate S-2765 hydrolysis as described (47). Negative controls included reactions missing the enzyme, reactions missing platelets, and reactions using unstimulated platelets.…”
Section: Fxa Generationmentioning
confidence: 99%